The theorization of organized criminality: contributions to a scientific discussion (Brazilian Journal of Police Sciences, 2022)
The theorization of organized criminality has been developed according to various perspectives – legal, sociological, political and economic – but underlying all of them there is a common problem concerning the construction of the concept of its object. Thepurpose of this article is to discuss some theoretical categories that can contribute to a better understanding of the concept of organized crime generally assumed in different studies. Our proposal uses some fundamental notions that we find in the theoretical discussion of science in general – such as paradigm, methodological programs and researchtraditions – with which we hope to contribute to a better scientific discussion on thesubject. In the end, based on these notions, we hope to make it clear that the understanding of organized criminality, considered here as a managerial concept of the problem of contemporary crime, presupposes understanding the systemic paradigm underlying itstheorization, in whatever path it follows.
Keywords: concept; theory; tradition; program; paradigm